(untitled) (Global Journal of Medical Research, 2011)
Through this research, the frequency of the primary hypolactasia phenotype has been determined and it includes the Albanian pupils in Macedonia from 7 to 12 years of age, as a result of the existence of the LacR allele. The correlation between the lactose maldigestion prevalence and the ageadvancement changes has also been analyzed. The research included 115 primar school children in Macedonia at the age of 7 to 12 years of Albanian nationality. The glucose level in them was measured before and 40 minutes after the input of 200 â€“ 220 ml of milk on an empty stomach, or 2 grams of lactose per one kilogram body weight. The emergence of clinical signs, such as glucose level increases with less than 1.1 mmol/lŁ, stomachaches, belly bulge, diarrhea, etc., have been considered as determining parameters of the existence of primary hypolactasia and LacR allele in the persons in question. The result is that the average of the primary hypolactasia phenotype in the Albanian population sample in Macedonia which underwent the analysis has been represented in 71.22% of the cases.